Anti-fouling ceramic glaze, ceramic and preparation method thereof
Through the combination of materials such as kaolin and modification additives, the problem of insufficient stain resistance and wear resistance of ceramic products is solved, which significantly improves the performance stability of ceramic products under humidity, heat, acid and corrosion conditions, and extends the service life of the product.
Patent Information
- Application Number
- CN202411357806.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Existing ceramic products have poor stain resistance, insufficient wear resistance and flexural strength, and poor performance stability under humid and heat and acid corrosion conditions, which limits the efficiency of the product.
Anti-fouling ceramic glaze composed of kaolin, sodium feldspar, calcium carbonate, mullite, firing talc powder and modification additives is mixed with nano-silica proton irradiation treatment and dopamine solution, combined with silicon carbide whiskers Potassium permanganate and lanthanum chloride treatment, combined with silane coupling agent, citric acid, sodium dodecylbenzenesulfonate and chitosan solutions, to form a modified solution to enhance the stain resistance and wear resistance of the ceramic body sex.
It significantly improves the stain resistance, wear resistance and bending strength of ceramic products, improves the performance stability under humid and heat, acid and corrosion conditions, and extends the service life of the product.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to an anti-fouling ceramic glaze, ceramics and a preparation method thereof. Background Art
[0002] Ceramics is a general term for pottery and porcelain. People invented pottery as early as the Neolithic Age about 8,000 years ago. Common ceramic materials include clay, alumina, kaolin, etc. Ceramic materials are generally hard but less plastic. In addition to being used in tableware and decoration, ceramics also play an important role in the development of science and technology. Ceramic raw materials are made by quenching clay, a large amount of resources originally available on the earth.
[0003] The existing ceramic glazes used in ceramics have poor stain resistance, and the ceramic products also have poor wear resistance and bending strength. When the products are placed under hot, humid and acidic conditions, the product performance stability deteriorates, limiting the product's efficiency. Based on this, the present invention further improves and processes the products. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide an anti-fouling ceramic glaze, ceramics and a preparation method thereof to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides an anti-fouling ceramic glaze, comprising the following raw materials in parts by weight:
[0007] 12-15 parts of kaolin, 12-15 parts of albite, 4-7 parts of calcium carbonate, 3-5 parts of mullite, 1-3 parts of calcined talc and 3-5 parts of modifying additives.
[0008] Preferably, the preparation method of the modified additive is:
[0009] S11: irradiating the nano-silicon dioxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed; mixing the irradiated nano-silicon dioxide and the dopamine solution in a weight ratio of 3:7 to obtain a nano-silicon dioxide liquid;
[0010] S12: 4-7 parts of nano-silica liquid, 2-5 parts of barium nitrate aqueous solution, 2-4 parts of carboxymethyl cellulose, and 2-4 parts of flake graphene are fully ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive.
[0011] Preferably, the mass fraction of the dopamine solution is 2-5%; the mass fraction of the barium nitrate aqueous solution is 3-6%.
[0012] The present invention also provides a method for preparing anti-fouling ceramics, using the anti-fouling ceramic glaze, comprising the following steps:
[0013] Step 1: Preparation of ceramic body:
[0014] a. Weigh the raw materials by weight:
[0015] 30-40 parts of quartz, 10-15 parts of potassium feldspar, 10-15 parts of calcined talc, 10-15 parts of pyrophyllite, 6-10 parts of a modifier for adjusting silicon carbide whiskers, and 2-4 parts of zinc oxide;
[0016] b. Mix the raw materials weighed above, and then ball-mill them with water as the ball-milling medium for 2 hours at a ball-milling speed of 1000 r / min. After the ball-milling is completed, dry, pass through a 100-mesh sieve, and then press into shape to obtain a ceramic body;
[0017] Step 2: Apply anti-fouling ceramic glaze on the surface of the ceramic body, with a glaze amount of 200-220g / m 2 , to obtain a glaze body;
[0018] Step 3: The glaze body is finally sintered at a temperature of 1250-1270°C for 1 hour to obtain anti-fouling ceramics.
[0019] Preferably, the preparation method of the silicon carbide whisker-adjusting modifier is:
[0020] S01: Stir and mix the silicon carbide whiskers in a sufficient amount of a 3-5% by mass potassium permanganate solution, then wash and dry to obtain dry silicon carbide whiskers;
[0021] The dried silicon carbide whiskers are immersed in a lanthanum chloride solution with a mass of 4-7 times the total mass of the dried silicon carbide whiskers, and then ultrasonically treated. After the immersion is completed, the solution is filtered and dried to obtain a lanthanum-doped silicon carbide whisker agent.
[0022] S02: adding 1-3 parts of silane coupling agent and 1-2 parts of citric acid to 4-7 parts of 6% by mass sodium dodecylbenzene sulfonate solution, and then adding 2-4 parts of chitosan solution and blending thoroughly to obtain a modified solution;
[0023] S03: stirring and modifying the lanthanum-doped silicon carbide whisker agent and the modifying liquid in a weight ratio of 2:5, and after the stirring is completed, washing and drying to obtain a modified silicon carbide whisker body;
[0024] S04: The modified silicon carbide whisker body and the regulating liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a silicon carbide whisker regulating modifier.
[0025] Preferably, the immersion power of the immersion ultrasonic treatment is 350-400W, and the immersion time is 30-40min; the stirring speed of the stirring modification treatment is 450-550r / min, and the stirring time is 25-35min.
[0026] Preferably, the mass fraction of the lanthanum chloride solution is 3-6%; the mass fraction of the chitosan solution is 2-5%; and the silane coupling agent is silane coupling agent KH560.
[0027] Preferably, the conditioning solution comprises the following raw materials in parts by weight:
[0028] 1-3 parts of nano-wollastonite, 2-5 parts of yttrium oxide, 4-7 parts of sodium alginate solution, 2-4 parts of nano-mica powder and 1-3 parts of nano-silica sol.
[0029] Preferably, the mass fraction of the sodium alginate solution is 5-8%.
[0030] The present invention also provides an anti-fouling ceramic, which is prepared by the preparation method of the anti-fouling ceramic.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The ceramic with anti-fouling ceramic glaze of the present invention is made of ceramic body and glaze. The ceramic body is composed of quartz, potassium feldspar, calcined talc, pyrophyllite, silicon carbide whisker adjusted modifier and zinc oxide raw material. Through the coordination and mutual assistance between the raw materials, the bending strength and wear resistance of the body matrix are enhanced, and the product has excellent performance stability under wet heat and acid corrosion conditions;
[0033] 2. The silicon carbide whisker modifier used for adjusting the silicon carbide whisker is treated with potassium permanganate solution to optimize its activity performance, and then immersed in lanthanum chloride solution for ultrasonic treatment to further improve the activity of the silicon carbide whisker, thereby improving the coordination effect of the whisker and the modifying solution. The silane coupling agent, citric acid, sodium dodecylbenzene sulfonate solution and chitosan solution in the modifying solution are blended and prepared with each other to work together to enhance the dispersion and activity performance of the whisker, thereby better coordinating and enhancing the performance with the adjusting solution. The nano-wollastonite, yttrium oxide, sodium alginate solution, nano-mica powder and nano-silica sol in the adjusting solution are blended and prepared, and the lamellar nano-mica powder is matched with the needle-shaped wollastonite, and the yttrium oxide and sodium alginate solution are coordinated. Through the coordination and mutual assistance between the raw materials, the whisker structure is strengthened, so that the performance of the system is further improved.
[0034] 3. The ceramic glaze is blended with kaolin, albite, calcium carbonate, mullite, calcined talc and modified additives. The raw materials are matched with each other to enhance the coordination effect between the glaze layer and the base layer, improve the anti-fouling property of the glaze layer, and improve the overall bending strength and wear resistance of the product. The product also has significant performance stability under hot and humid conditions and acid corrosion conditions.
[0035] 4. The modified additive uses nano-silicon dioxide that is irradiated in a proton irradiation box before being treated to optimize the activity of the nano-silicon dioxide. The nano-silicon dioxide is combined with a dopamine solution, and the barium nitrate aqueous solution, carboxymethyl cellulose, and flaky graphene are blended and fully ball-milled. The flaky structure of the flaky graphene is coordinated with the barium nitrate aqueous solution and nano-silicon dioxide to further enhance the anti-fouling performance of the system and the matching effect of the product glaze layer and the substrate layer, thereby further improving the performance of the product. DETAILED DESCRIPTION
[0036] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The embodiment of the present invention provides an anti-fouling ceramic glaze, comprising the following raw materials in parts by weight:
[0038] 12-15 parts of kaolin, 12-15 parts of albite, 4-7 parts of calcium carbonate, 3-5 parts of mullite, 1-3 parts of calcined talc and 3-5 parts of modifying additives.
[0039] The preparation method of the modified additive in this embodiment is:
[0040] S11: irradiating the nano-silicon dioxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed; mixing the irradiated nano-silicon dioxide and the dopamine solution in a weight ratio of 3:7 to obtain a nano-silicon dioxide liquid;
[0041] S12: 4-7 parts of nano-silica liquid, 2-5 parts of barium nitrate aqueous solution, 2-4 parts of carboxymethyl cellulose, and 2-4 parts of flake graphene are fully ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive.
[0042] The mass fraction of the dopamine solution in this embodiment is 2-5%; the mass fraction of the barium nitrate aqueous solution is 3-6%.
[0043] The embodiment of the present invention further provides a method for preparing anti-fouling ceramics, using the anti-fouling ceramic glaze, comprising the following steps:
[0044] Step 1: Preparation of ceramic body:
[0045] a. Weigh the raw materials by weight:
[0046] 30-40 parts of quartz, 10-15 parts of potassium feldspar, 10-15 parts of calcined talc, 10-15 parts of pyrophyllite, 6-10 parts of a modifier for adjusting silicon carbide whiskers, and 2-4 parts of zinc oxide;
[0047] b. Mix the raw materials weighed above, and then ball-mill them with water as the ball-milling medium for 2 hours at a ball-milling speed of 1000 r / min. After the ball-milling is completed, dry, pass through a 100-mesh sieve, and then press into shape to obtain a ceramic body;
[0048] Step 2: Apply anti-fouling ceramic glaze on the surface of the ceramic body, with a glaze amount of 200-220g / m 2 , to obtain a glaze body;
[0049] Step 3: The glaze body is finally sintered at a temperature of 1250-1270°C for 1 hour to obtain anti-fouling ceramics.
[0050] The preparation method of the silicon carbide whisker-adjusting modifier in this embodiment is:
[0051] S01: Stir and mix the silicon carbide whiskers in a sufficient amount of a 3-5% by mass potassium permanganate solution, then wash and dry to obtain dry silicon carbide whiskers;
[0052] The dried silicon carbide whiskers are immersed in a lanthanum chloride solution with a mass of 4-7 times the total mass of the dried silicon carbide whiskers, and then ultrasonically treated. After the immersion is completed, the solution is filtered and dried to obtain a lanthanum-doped silicon carbide whisker agent.
[0053] S02: adding 1-3 parts of silane coupling agent and 1-2 parts of citric acid to 4-7 parts of 6% by mass sodium dodecylbenzene sulfonate solution, and then adding 2-4 parts of chitosan solution and blending thoroughly to obtain a modified solution;
[0054] S03: stirring and modifying the lanthanum-doped silicon carbide whisker agent and the modifying liquid in a weight ratio of 2:5, and after the stirring is completed, washing and drying to obtain a modified silicon carbide whisker body;
[0055] S04: The modified silicon carbide whisker body and the regulating liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a silicon carbide whisker regulating modifier.
[0056] The immersion power of the immersion ultrasonic treatment in this embodiment is 350-400W, and the immersion time is 30-40min; the stirring speed of the stirring modification treatment is 450-550r / min, and the stirring time is 25-35min.
[0057] The mass fraction of the lanthanum chloride solution in this embodiment is 3-6%; the mass fraction of the chitosan solution is 2-5%; and the silane coupling agent is silane coupling agent KH560.
[0058] The conditioning solution in this embodiment includes the following raw materials in parts by weight:
[0059] 1-3 parts of nano-wollastonite, 2-5 parts of yttrium oxide, 4-7 parts of sodium alginate solution, 2-4 parts of nano-mica powder and 1-3 parts of nano-silica sol.
[0060] The mass fraction of the sodium alginate solution in this embodiment is 5-8%.
[0061] This embodiment also provides an anti-fouling ceramic, which is prepared by the above-mentioned method for preparing an anti-fouling ceramic.
[0062] Example 1: An anti-fouling ceramic glaze comprising the following raw materials in parts by weight:
[0063] 12 parts of kaolin, 12 parts of albite, 4 parts of calcium carbonate, 3 parts of mullite, 1 part of calcined talc and 3 parts of modifying additives.
[0064] The preparation method of the modified additive in this embodiment is:
[0065] S11: irradiating the nano-silicon dioxide in a proton irradiation box for 5 minutes at an irradiation power of 350 W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed; mixing the irradiated nano-silicon dioxide and the dopamine solution in a weight ratio of 3:7 to obtain a nano-silicon dioxide liquid;
[0066] S12: 4 parts of nano-silica liquid, 2 parts of barium nitrate aqueous solution, 2 parts of carboxymethyl cellulose and 2 parts of flake graphene are mixed and ball-milled thoroughly at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive.
[0067] The mass fraction of the dopamine solution in this embodiment is 2%; the mass fraction of the barium nitrate aqueous solution is 3%.
[0068] This embodiment also provides a method for preparing an anti-fouling ceramic, using the anti-fouling ceramic glaze, comprising the following steps:
[0069] Step 1: Preparation of ceramic body:
[0070] a. Weigh the raw materials by weight:
[0071] 30 parts of quartz, 10 parts of potassium feldspar, 10 parts of calcined talc, 10 parts of pyrophyllite, 6 parts of modifier adjusted by silicon carbide whiskers, and 2 parts of zinc oxide;
[0072] b. Mix the raw materials weighed above, and then ball-mill them with water as the ball-milling medium for 2 hours at a ball-milling speed of 1000 r / min. After the ball-milling is completed, dry, pass through a 100-mesh sieve, and then press into shape to obtain a ceramic body;
[0073] Step 2: Apply anti-fouling ceramic glaze on the surface of the ceramic body, with a glaze amount of 200g / m 2 , to obtain a glaze body;
[0074] Step 3: The glaze body is finally sintered at a temperature of 1250°C for 1 hour to obtain anti-fouling ceramics.
[0075] The preparation method of the silicon carbide whisker-adjusting modifier in this embodiment is:
[0076] S01: Stir and mix the silicon carbide whiskers in a sufficient amount of 3% by mass potassium permanganate solution, then wash and dry to obtain dry silicon carbide whiskers;
[0077] The dried silicon carbide whiskers are immersed in a lanthanum chloride solution with a mass 4 times that of the total mass of the dried silicon carbide whiskers, and then ultrasonically treated. After the immersion is completed, the solution is filtered and dried to obtain a lanthanum-doped silicon carbide whisker agent.
[0078] S02: adding 1 part of silane coupling agent and 1 part of citric acid to 4 parts of 6% by mass sodium dodecylbenzene sulfonate solution, and then adding 2 parts of chitosan solution and blending thoroughly to obtain a modified solution;
[0079] S03: stirring and modifying the lanthanum-doped silicon carbide whisker agent and the modifying liquid in a weight ratio of 2:5, and after the stirring is completed, washing and drying to obtain a modified silicon carbide whisker body;
[0080] S04: The modified silicon carbide whisker body and the regulating liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a silicon carbide whisker regulating modifier.
[0081] The immersion power of the immersion ultrasonic treatment in this embodiment is 350W, and the immersion time is 30min; the stirring speed of the stirring modification treatment is 450r / min, and the stirring time is 25min.
[0082] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the mass fraction of the chitosan solution is 2%; and the silane coupling agent is silane coupling agent KH560.
[0083] The conditioning solution in this embodiment includes the following raw materials in parts by weight:
[0084] 1 part of nano-wollastonite, 2 parts of yttrium oxide, 4 parts of sodium alginate solution, 2 parts of nano-mica powder and 1 part of nano-silica sol.
[0085] The mass fraction of the sodium alginate solution in this embodiment is 5%.
[0086] This embodiment also provides an anti-fouling ceramic, which is prepared by the above-mentioned method for preparing an anti-fouling ceramic.
[0087] Example 2: An anti-fouling ceramic glaze comprising the following raw materials in parts by weight:
[0088] 15 parts of kaolin, 15 parts of albite, 7 parts of calcium carbonate, 5 parts of mullite, 3 parts of calcined talc and 5 parts of modifying additives.
[0089] The preparation method of the modified additive in this embodiment is:
[0090] S11: irradiating the nano-silicon dioxide in a proton irradiation box for 10 minutes at an irradiation power of 400 W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed; mixing the irradiated nano-silicon dioxide and the dopamine solution in a weight ratio of 3:7 to obtain a nano-silicon dioxide liquid;
[0091] S12: 7 parts of nano-silica liquid, 5 parts of barium nitrate aqueous solution, 4 parts of carboxymethyl cellulose and 4 parts of flake graphene are mixed and ball-milled thoroughly at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive.
[0092] The mass fraction of the dopamine solution in this embodiment is 5%; the mass fraction of the barium nitrate aqueous solution is 6%.
[0093] This embodiment also provides a method for preparing an anti-fouling ceramic, using the anti-fouling ceramic glaze, comprising the following steps:
[0094] Step 1: Preparation of ceramic body:
[0095] a. Weigh the raw materials by weight:
[0096] 40 parts of quartz, 15 parts of potassium feldspar, 15 parts of calcined talc, 15 parts of pyrophyllite, 10 parts of a modifier for adjusting silicon carbide whiskers, and 4 parts of zinc oxide;
[0097] b. Mix the raw materials weighed above, and then ball-mill them with water as the ball-milling medium for 2 hours at a ball-milling speed of 1000 r / min. After the ball-milling is completed, dry, pass through a 100-mesh sieve, and then press into shape to obtain a ceramic body;
[0098] Step 2: Apply anti-fouling ceramic glaze on the surface of the ceramic body, with a glaze amount of 220g / m 2 , to obtain a glaze body;
[0099] Step 3: The glaze body is finally sintered at a temperature of 1270°C for 1 hour to obtain anti-fouling ceramics.
[0100] The preparation method of the silicon carbide whisker-adjusting modifier in this embodiment is:
[0101] S01: Stir and mix the silicon carbide whiskers in a sufficient amount of 5% by mass potassium permanganate solution, then wash and dry to obtain dry silicon carbide whiskers;
[0102] The dried silicon carbide whiskers are immersed in a lanthanum chloride solution with a mass 7 times that of the total mass of the dried silicon carbide whiskers, and then ultrasonically treated. After the immersion is completed, the solution is filtered and dried to obtain a lanthanum-doped silicon carbide whisker agent.
[0103] S02: adding 3 parts of silane coupling agent and 2 parts of citric acid to 7 parts of 6% sodium dodecylbenzene sulfonate solution, and then adding 4 parts of chitosan solution and mixing thoroughly to obtain a modified solution;
[0104] S03: stirring and modifying the lanthanum-doped silicon carbide whisker agent and the modifying liquid in a weight ratio of 2:5, and after the stirring is completed, washing and drying to obtain a modified silicon carbide whisker body;
[0105] S04: The modified silicon carbide whisker body and the regulating liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a silicon carbide whisker regulating modifier.
[0106] The immersion power of the immersion ultrasonic treatment in this embodiment is 400 W, and the immersion time is 40 min; the stirring speed of the stirring modification treatment is 550 r / min, and the stirring time is 35 min.
[0107] The mass fraction of the lanthanum chloride solution in this embodiment is 6%; the mass fraction of the chitosan solution is 5%; and the silane coupling agent is silane coupling agent KH560.
[0108] The conditioning solution in this embodiment includes the following raw materials in parts by weight:
[0109] 3 parts of nano-wollastonite, 5 parts of yttrium oxide, 7 parts of sodium alginate solution, 4 parts of nano-mica powder and 3 parts of nano-silica sol.
[0110] The mass fraction of the sodium alginate solution in this embodiment is 8%.
[0111] This embodiment also provides an anti-fouling ceramic, which is prepared by the above-mentioned method for preparing an anti-fouling ceramic.
[0112] Example 3: An anti-fouling ceramic glaze used in a method for preparing an anti-fouling ceramic, the anti-fouling ceramic glaze comprising the following raw materials in parts by weight:
[0113] 13.5 parts of kaolin, 13.5 parts of albite, 5.5 parts of calcium carbonate, 4 parts of mullite, 2 parts of calcined talc and 4 parts of modifying additives.
[0114] The preparation method of the modified additive in this embodiment is:
[0115] S11: irradiating the nano-silicon dioxide in a proton irradiation box for 7.5 minutes at an irradiation power of 370 W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed; mixing the irradiated nano-silicon dioxide and the dopamine solution in a weight ratio of 3:7 to obtain a nano-silicon dioxide liquid;
[0116] S12: 5.5 parts of nano-silica liquid, 3.5 parts of barium nitrate aqueous solution, 3 parts of carboxymethyl cellulose and 3 parts of flake graphene are mixed and ball-milled thoroughly at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive.
[0117] The mass fraction of the dopamine solution in this embodiment is 3.5%; the mass fraction of the barium nitrate aqueous solution is 4.5%.
[0118] This embodiment also provides a method for preparing an anti-fouling ceramic, using the anti-fouling ceramic glaze, comprising the following steps:
[0119] Step 1: Preparation of ceramic body:
[0120] a. Weigh the raw materials by weight:
[0121] 35 parts of quartz, 12.5 parts of potassium feldspar, 12.5 parts of calcined talc, 12.5 parts of pyrophyllite, 8 parts of a modifier for adjusting silicon carbide whiskers, and 3 parts of zinc oxide;
[0122] b. Mix the raw materials weighed above, and then ball-mill them with water as the ball-milling medium for 2 hours at a ball-milling speed of 1000 r / min. After the ball-milling is completed, dry, pass through a 100-mesh sieve, and then press into shape to obtain a ceramic body;
[0123] Step 2: Apply anti-fouling ceramic glaze on the surface of the ceramic body, with a glaze amount of 210g / m 2 , to obtain a glaze body;
[0124] Step 3: The glaze body is finally sintered at a temperature of 1260°C for 1 hour to obtain anti-fouling ceramics.
[0125] The preparation method of the silicon carbide whisker-adjusting modifier in this embodiment is:
[0126] S01: Stir and mix the silicon carbide whiskers in a sufficient amount of 4% by mass potassium permanganate solution, then wash and dry to obtain dry silicon carbide whiskers;
[0127] The dried silicon carbide whiskers are immersed in a lanthanum chloride solution with a mass 5.5 times that of the total mass of the dried silicon carbide whiskers, and then ultrasonically treated. After the immersion is completed, the solution is filtered and dried to obtain a lanthanum-doped silicon carbide whisker agent.
[0128] S02: adding 2 parts of silane coupling agent and 1.5 parts of citric acid to 5.5 parts of 6% sodium dodecylbenzene sulfonate solution, and then adding 3 parts of chitosan solution and blending thoroughly to obtain a modified solution;
[0129] S03: stirring and modifying the lanthanum-doped silicon carbide whisker agent and the modifying liquid in a weight ratio of 2:5, and after the stirring is completed, washing and drying to obtain a modified silicon carbide whisker body;
[0130] S04: The modified silicon carbide whisker body and the regulating liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a silicon carbide whisker regulating modifier.
[0131] The immersion power of the immersion ultrasonic treatment in this embodiment is 370W, and the immersion time is 35min; the stirring speed of the stirring modification treatment is 500r / min, and the stirring time is 30min.
[0132] The mass fraction of the lanthanum chloride solution in this embodiment is 4.5%; the mass fraction of the chitosan solution is 3.5%; and the silane coupling agent is silane coupling agent KH560.
[0133] The conditioning solution in this embodiment includes the following raw materials in parts by weight:
[0134] 2 parts of nano-wollastonite, 3.5 parts of yttrium oxide, 5.5 parts of sodium alginate solution, 3 parts of nano-mica powder and 2 parts of nano-silica sol.
[0135] The mass fraction of the sodium alginate solution in this embodiment is 6.5%.
[0136] This embodiment also provides an anti-fouling ceramic, which is prepared by the above-mentioned method for preparing an anti-fouling ceramic.
[0137] Comparative Example 1:
[0138] The difference from Example 3 is that no modifier for adjusting the silicon carbide whiskers is added to the ceramic body.
[0139] Comparative Example 2:
[0140] The difference from Example 3 is that S01 treatment was not used in the preparation of the modifier for adjusting the silicon carbide whiskers.
[0141] Comparative Example 3:
[0142] The difference from Example 3 is that no modifying liquid treatment is used in the preparation of the modifier for adjusting the silicon carbide whiskers.
[0143] Comparative Example 4:
[0144] The difference from Example 3 is that no silane coupling agent or chitosan solution is added to the modified liquid.
[0145] Comparative Example 5:
[0146] The difference from Example 3 is that no conditioning liquid treatment is used in the preparation of the modifier for conditioning the silicon carbide whiskers.
[0147] Comparative Example 6:
[0148] The difference from Example 3 is that no modifying additive is added to the ceramic glaze.
[0149] Comparative Example 7:
[0150] The difference from Example 3 is that no barium nitrate aqueous solution is added in the preparation of the modified additive.
[0151] Comparative Example 8:
[0152] The difference from Example 3 is that no nano-silicon dioxide liquid is added in the preparation of the modified additive.
[0153] Comparative Example 9:
[0154] The difference from Example 3 is that no flaky graphene is added in the preparation of the modified additive.
[0155] The ceramic products of Examples 1 to 3 and Comparative Examples 1 to 9 were subjected to conventional performance tests, and were placed under 10% humidity and 55°C temperature conditions for 24 hours, and then placed under 2% acid corrosion conditions for 24 hours, which was one cycle. The test was repeated 10 times to test the moisture and heat resistance and acid corrosion resistance of the products. The test results are shown in Table 1.
[0156] Table 1: Performance test results of ceramic products of Examples 1 to 3 and Comparative Examples 1 to 9:
[0157]
[0158] As can be seen from Table 1, the product of Example 3 has excellent anti-fouling properties, as well as excellent wear resistance and flexural strength properties, and the three can be improved in a coordinated manner. In addition, the product has significant effects on moisture resistance, heat resistance, acid corrosion resistance and stability.
[0159] It can be seen from Comparative Examples 1 to 9 and Example 3 that the ceramic body is not modified by adding silicon carbide whiskers, and the wear resistance and anti-fouling strength of the product have a significant deterioration trend, and the product performance stability deteriorates more significantly under the conditions of heat and humidity resistance and acid corrosion resistance;
[0160] Without adding modifying additives to ceramic glaze, the anti-fouling performance of the product deteriorates significantly. By using a modifier adjusted by silicon carbide whiskers and modifying additives, the performance of the product can be improved in a coordinated manner.
[0161] The performance of the product also showed different degrees of deterioration trend when S01 treatment was not used in the preparation of the modifier for adjusting the silicon carbide whisker, the modification liquid treatment was not used in the preparation of the modifier for adjusting the silicon carbide whisker, the silane coupling agent and chitosan solution were not added to the modification liquid, and the adjustment liquid treatment was not used in the preparation of the modifier for adjusting the silicon carbide whisker. The performance of the product showed a more obvious deterioration trend when the adjustment liquid treatment was not used;
[0162] No barium nitrate aqueous solution, no nano-silica liquid, and no flaky graphene were added in the preparation of the modified additive. The performance of the modified additive products prepared by different methods tended to deteriorate. Only by using the modified additive of the present invention, the product performance effect was the most significant.
[0163] Since the regulating liquid has a significant effect on the performance of the product, further research is conducted on this.
[0164] Experimental Example 1:
[0165] The only difference from Example 3 is that no nano-wollastonite is added to the conditioning solution.
[0166] Experimental Example 2:
[0167] The only difference from Example 3 is that yttrium oxide is not added to the conditioning solution.
[0168] Experimental Example 3:
[0169] The only difference from Example 3 is that no nano-mica powder is added to the conditioning solution.
[0170] Experimental Example 4:
[0171] The only difference from Example 3 is that no nano silica sol is added to the conditioning solution.
[0172] Experimental Example 5:
[0173] The only difference from Example 3 is that the sodium alginate solution in the conditioning solution is replaced by water.
[0174] The ceramic products of Experimental Examples 1 to 5 were subjected to conventional performance tests, and were placed under 10% humidity and 55°C temperature conditions for 24 hours, and then placed under 2% acid corrosion conditions for 24 hours, which was one cycle. The cycle test was repeated 10 times to test the products' resistance to moisture and heat, and acid corrosion stability. The test results are shown in Table 2.
[0175] Table 2: Ceramic product performance test results of Experimental Examples 1 to 5:
[0176]
[0177] As can be seen from Table 2, adding nano-wollastonite to the regulating liquid can significantly promote the performance of the product under normal conditions, while adding nano-mica powder to the regulating liquid can significantly promote the performance of the product under conditions of moisture and heat resistance and acid and corrosion resistance. The performance effect of the product is most significant when nano-wollastonite in the regulating liquid is matched with nano-mica powder as a matrix agent, and yttrium oxide, nano-silica sol and sodium alginate solution are combined. The regulating liquid obtained by mutual coordination and synergy between the raw materials has the most significant effect on the product performance. The raw materials in the regulating liquid composition are indispensable, and other methods are used to replace them, which are not as significant as the effect of the present invention.
[0178] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0179] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A stain-resistant ceramic glaze, characterized in that: It includes the following raw materials in parts by weight: 12-15 parts of kaolin, 12-15 parts of albite, 4-7 parts of calcium carbonate, 3-5 parts of mullite, 1-3 parts of calcined talc and 3-5 parts of modifying additives; The preparation method of the modified additive is: S11: irradiating the nano-silicon dioxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed; mixing the irradiated nano-silicon dioxide and the dopamine solution in a weight ratio of 3:7 to obtain a nano-silicon dioxide liquid; S12: 4-7 parts of nano-silica liquid, 2-5 parts of barium nitrate aqueous solution, 2-4 parts of carboxymethyl cellulose, and 2-4 parts of flake graphene are fully ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive.
2. The anti-fouling ceramic glaze according to claim 1, characterized in that: The mass fraction of the dopamine solution is 2-5%; the mass fraction of the barium nitrate aqueous solution is 3-6%.
3. A method for preparing anti-fouling ceramics, characterized in that: Using the anti-fouling ceramic glaze according to any one of claims 1 to 2 comprises the following steps: Step 1: Preparation of ceramic body: a. Weigh the raw materials by weight: 30-40 parts of quartz, 10-15 parts of potassium feldspar, 10-15 parts of calcined talc, 10-15 parts of pyrophyllite, 6-10 parts of a modifier for adjusting silicon carbide whiskers, and 2-4 parts of zinc oxide; b. Mix the raw materials weighed above, and then ball-mill them with water as the ball-milling medium for 2 hours at a ball-milling speed of 1000 r / min. After the ball-milling is completed, dry, pass through a 100-mesh sieve, and then press into shape to obtain a ceramic body; Step 2: Apply anti-fouling ceramic glaze on the surface of the ceramic body, with a glaze amount of 200-220g / m 2 , to obtain a glaze body; Step 3: The glaze body is finally sintered at a temperature of 1250-1270°C for 1 hour to obtain anti-fouling ceramics; The preparation method of the silicon carbide whisker-adjusting modifier is: S01: Stir and mix the silicon carbide whiskers in a sufficient amount of a 3-5% by mass potassium permanganate solution, then wash and dry to obtain dry silicon carbide whiskers; The dried silicon carbide whiskers are immersed in a lanthanum chloride solution with a mass of 4-7 times the total mass of the dried silicon carbide whiskers, and then ultrasonically treated. After the immersion is completed, the solution is filtered and dried to obtain a lanthanum-doped silicon carbide whisker agent. S02: adding 1-3 parts of silane coupling agent and 1-2 parts of citric acid to 4-7 parts of 6% by mass sodium dodecylbenzene sulfonate solution, and then adding 2-4 parts of chitosan solution and blending thoroughly to obtain a modified solution; S03: stirring and modifying the lanthanum-doped silicon carbide whisker agent and the modifying liquid in a weight ratio of 2:5, and after the stirring is completed, washing and drying to obtain a modified silicon carbide whisker body; S04: The modified silicon carbide whisker body and the conditioning liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a modifier for regulating silicon carbide whiskers; The conditioning solution comprises the following raw materials in parts by weight: 1-3 parts of nano-wollastonite, 2-5 parts of yttrium oxide, 4-7 parts of sodium alginate solution, 2-4 parts of nano-mica powder and 1-3 parts of nano-silica sol.
4. The method for preparing an anti-fouling ceramic according to claim 3, characterized in that: The immersion power of the immersion ultrasonic treatment is 350-400W, and the immersion time is 30-40min; the stirring speed of the stirring modification treatment is 450-550r / min, and the stirring time is 25-35min.
5. The method for preparing an anti-fouling ceramic according to claim 3, characterized in that: The mass fraction of the lanthanum chloride solution is 3-6%; the mass fraction of the chitosan solution is 2-5%; and the silane coupling agent is silane coupling agent KH560.
6. The method for preparing an anti-fouling ceramic according to claim 3, characterized in that: The mass fraction of the sodium alginate solution is 5-8%.
7. An anti-fouling ceramic prepared by the method for preparing an anti-fouling ceramic according to claim 3.
Citation Information
Patent Citations
Glazed ceramic product and preparation method thereof
CN111233435A
Natural granite-imitated ceramic tile with antifouling effect and preparation method thereof
CN112250308A